Entre verrinas e ditirambos: maternagem nos discursos normativos: São Paulo, 1925-1940 - Colucci, Sandra Regina (2016)
This research aimed to capture the constitution movement of different practices of mothering through fragments filtered by the hegemonic consciousness of documents, seeking historicizing the construction of the meanings assigned to it in his subjective process. The life of the city scaled the perspective of social history through different eyes, in the diversity of languages and the multiplicity of their code authorizes the analysis of the relationships established by different speeches that wove responsibility networks and guilt mothers front of child crime, forms of female labor, disease, death and food practices. In this sense, the theme of Between blame and praise: mothering in normative discourses" appears woven in the pursuit of building meanings to different feminine care practices with their children in ways of working, living, live, to have fun, to eat, to women's daily lives. Our goal was to analyze the discourses that allow heterogeneous seek the local knowledge, perception of other times / places in concurrency multidirectional experiences, in the seizure of tensions and confrontations inherent experiences, as well as on the construction of representations in its multiple interference the strategies of social groups, producing new study references that allow the expansion of women's studies